Fabrication of high magnetic performance Feâ50Ni alloy by powder injection molding - Ali, M. (Bellwether Publishing, Ltd., 2020)
Feâ50Ni alloy is widely used for soft magnetic applications due to attractive magnetic properties. In this study, Feâ50Ni soft magnetic alloy was produced by powder injection molding. The influence of sintering parameters was investigated on the density, grain size, and magnetic properties. The injected parts were sintered at 1300â1375Â°C for 2â14Â h with subsequent controlled slow cooling. It has found that permeability and magnetic induction improved with increasing sintering time and temperature, whereas the coercivity was reduced significantly. The sintered density and grain size of 98 and 240Â Âµm were obtained in this study. Consequently, excellent magnetic properties of Feâ50Ni were achieved. The values of magnetic permeability and saturation induction were 50,240 and 1.52 T, respectively. Â© 2020 Taylor & Francis.